2007
DOI: 10.1111/j.1468-4187.2006.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The delivery of a survivors’ group for learning disabled women with significant learning disabilities who have been sexually abused

Abstract: Accessible summary• People with learning disabilities are more likely to experience sexual things happening to them when they do not want them to. This is called sexual abuse. • A group was started to help women who have been sexually abused. The group met once a week and lasted for 20 weeks. • Women who were interested in attending this group were given information about it and asked on three separate occasions if they wanted to attend. • Seven women with learning disabilities took part in the group and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Other studies have similarly identified a lack of referrals to services, such as counselling and therapy, to support disabled people once they have reported incidents to the police (Sequeira, 2006;Peckham et al, 2007). In other instances, disabled people may receive referrals from the police to support services but did not experience real redress:…”
Section: Responses From Criminal Justice Agenciesmentioning
confidence: 88%
“…Other studies have similarly identified a lack of referrals to services, such as counselling and therapy, to support disabled people once they have reported incidents to the police (Sequeira, 2006;Peckham et al, 2007). In other instances, disabled people may receive referrals from the police to support services but did not experience real redress:…”
Section: Responses From Criminal Justice Agenciesmentioning
confidence: 88%
“…The late twentieth and early twenty-first centuries have seen a late flowering of interest in psychotherapy with people with intellectual disabilities (Alvarez, 1992;Andrew, 2003;Beail, 1998;Corbett, 1996;Corbett, Cottis, & Morris 1996;Cottis, 2009;De Groef & Heinmann, 1999;Frankish, 2009;Kahr, 2000;Linington, 2002;McGinnity & Banks, 2004;Peckham, Corbett, Howlett, McKee, & Pattison 2007;Sinason, 1992;Willner, 2005), with the establishment of clinics such as Respond, in London, and the birth of the United Kingdom Council for Psychotherapy (UKCP)-recognised Institute of Psychotherapy and Disability providing a national umbrella for clinicians working in the field.…”
Section: Psychotherapy and Intellectual Disabilitymentioning
confidence: 98%
“…However, they may lack the range of adaptive psychological coping strategies and supports to cope with such life events (Bicknell1983, Taylor et al 2008). People with ID are also at greater risk than their non-disabled counterparts of experiences of abuse and trauma (Peckham et al 2007, Robinson 2013) and such experiences are likely to be implicative in the development of a range of psychological and psychiatric disorders, including contributing to the development of disability or secondary handicap (Sinason 1992, Frankish 2013. While there is little evidence to show changes in the prevalence of psychological and psychiatric disorders at particular points over the life course, the clinical view is that, just as for people without ID, people with ID are particularly at risk for the development of difficulties at points of transition or crisis, such as changing school, moving from school to college, moving from living within a family unit to living in a more independent setting, changing jobs and being bereaved.…”
Section: Mental Health Psychological Well-being and Idmentioning
confidence: 99%
“…They highlight some of the complex issues in running a group for people with ID, some of which are similar to groups for people without ID (for example participants not liking each other, age difference between group members) and some of which were specific to this participant group (for example the wide range of cognitive ability of the participants). Peckham et al (2007) ran a group for women with ID who had experienced sexual abuse. The group lasted for 20 sessions and involved three stages, establishing relationships and the therapeutic alliance, psychoeducation and helping reprocess the trauma.…”
Section: Cbt and Angermentioning
confidence: 99%